The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1103/physrevb.101.094505
|View full text |Cite
|
Sign up to set email alerts
|

Odd-frequency superconductivity near a magnetic impurity in a conventional superconductor

Abstract: Superconductor-ferromagnetic heterostructures have been suggested as one of the most promising alternatives of realizing odd-frequency superconductivity. In this work we consider the limit of shrinking the ferromagnetic region to the limit of a single impurity embedded in a conventional superconductor, which gives raise to localized Yu-Shiba-Rusinov (YSR) bound states with energies inside the superconducting gap. We demonstrate that all the sufficient ingredients for generating odd-frequency pairing are presen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 63 publications
1
20
0
Order By: Relevance
“…We expect therefore superconductivity to be induced at the impurity site by the proximity effect. Because of the time-reversal symmetry breaking due to the magnetic field at the impurity, an odd-ω pair- ing component is expected to appear [4], similarly to the single-impurity case [31,32]. As the impurity electrons form the YSR bands, these should then display an odd-ω superconducting component in the superconducting function.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We expect therefore superconductivity to be induced at the impurity site by the proximity effect. Because of the time-reversal symmetry breaking due to the magnetic field at the impurity, an odd-ω pair- ing component is expected to appear [4], similarly to the single-impurity case [31,32]. As the impurity electrons form the YSR bands, these should then display an odd-ω superconducting component in the superconducting function.…”
Section: Resultsmentioning
confidence: 99%
“…One recent study has reported odd-ω superconductivity at the interface of a topological insulator with a conventional superconductor [29]. In another recent development, which builds upon earlier theoretical work [30,31], the presence of an odd-ω component in scanning tunneling spectroscopy (STS) has finally been reported in a system of a magnetic impurity in contact with a conventional superconductor [32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the transition between the doublet and the singlet ground state, the subgap states (also known as Yu-Shiba-Rusinov states) cross the Fermi level [24][25][26] leading to a super-current sign reversal, the so-called 0 − π transition [27][28][29][30][31]. At the ground state transition, BCS pair correlations are suppressed and the electron pairing is predominantly spin-triplet close to the impurity [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…In this discussion it is important to distinguish between existence of a superconducting condensate with an odd-frequency order parameter, i.e., with nonzero gap function, and oddfrequency pair correlations. The latter can occur when a frequency-even superconductor is placed in close proximity to a magnetic layer or when a magnetic impurity is placed on a conventional superconductor [10][11][12][13][14][15][16][17][18]. The spins of the conventional Cooper-pair electrons become rotated in the exchange field, leading to a spin-triplet component with time-odd parity [10,19].…”
Section: Introductionmentioning
confidence: 99%